Cyclic behavior of RC beams under artificial climate rapid freeze-thaw environment: A further research. (December 2022) - Wang, Jun-Yan; Rong, Xian-Liang; Zheng, Shan-Suo; Zhang, Yi-Xin; Dai, Kuang-Yu; Dong, Li-guo; Wang, Zi-Sheng
Abstract: Frost damage to concrete can make concrete beams more vulnerable under seismic forces. However, research on the seismic performance of frost-damaged reinforced concrete (RC) beams is still in its infancy. In this paper, the effects of freeze–thaw cycles (FTCs) and concrete strength on the seismic performance of frost-damaged RC beams are studied using an artificial rapid freeze–thaw climate and pseudo–static test in sequence. The seismic resistance of frost-damaged RC beams is assessed in the following respects: general damage behavior and failure pattern, hysteresis response, displacement, strength, cumulative energy consumption, and shear component. It turns out that, with the increase in the number of FTCs (NFTCs), the load and displacement under different characteristic states, ductility ratio, and cumulative energy consumption decrease stage by stage, while the shear distortion and the contribution of shear displacement under the entire cyclic loading process are progressively enhanced. Simultaneously, the strength of the cracking point is more susceptible to FTC action than to yield and peak points, and the declining rate of strength under different characteristic points gradually increases. Based on the test results, a calculation formula for the skeleton curve of frost-damaged RC beam–column is established, taking the influences of the pristine concrete strength, NFTCs, and axial force ratio into account.